Psychogenic Nonepileptic Seizures in Children with Epilepsy - Agarwal, Rajkumar; Shahid, Asim (Journal of Pediatric Epilepsy, 2018)
The occurrence of psychogenic seizures in a proportion of children with epilepsy has been well described. The diagnosis of simultaneous existence of nonepileptic and epileptic seizures is often challenging as the clinical features of these conditions may overlap. However, they differ significantly in terms of the underlying pathophysiology as well as management strategies. Timely recognition can prevent harmful treatments and potentially improve patient outcome. In this article, we focus on the epidemiology, clinical features as well as management of psychogenic seizures in children with epilepsy.
Keywords: nonepileptic seizures; epilepsy; video EEG; conversion disorder